Step
*
2
2
of Lemma
co-cons_one_one
1. T : Type
2. a : T
3. a' : T
4. b : colist(T)
5. b' : colist(T)
6. [a / b] = [a' / b'] ∈ colist(T)
7. [a / b] = [a' / b'] ∈ {z:colist(T)| (z = [a / b] ∈ colist(T)) ∧ (z = [a' / b'] ∈ colist(T))} 
8. tl([a / b]) = tl([a' / b']) ∈ colist(T)
⊢ b = b' ∈ colist(T)
BY
{ (RepUR ``co-cons`` -1 THEN Fold `cons` (-1) THEN Reduce -1) }
1
1. T : Type
2. a : T
3. a' : T
4. b : colist(T)
5. b' : colist(T)
6. [a / b] = [a' / b'] ∈ colist(T)
7. [a / b] = [a' / b'] ∈ {z:colist(T)| (z = [a / b] ∈ colist(T)) ∧ (z = [a' / b'] ∈ colist(T))} 
8. b = b' ∈ colist(T)
⊢ b = b' ∈ colist(T)
Latex:
Latex:
1.  T  :  Type
2.  a  :  T
3.  a'  :  T
4.  b  :  colist(T)
5.  b'  :  colist(T)
6.  [a  /  b]  =  [a'  /  b']
7.  [a  /  b]  =  [a'  /  b']
8.  tl([a  /  b])  =  tl([a'  /  b'])
\mvdash{}  b  =  b'
By
Latex:
(RepUR  ``co-cons``  -1  THEN  Fold  `cons`  (-1)  THEN  Reduce  -1)
Home
Index